2023
DOI: 10.3390/microorganisms11010216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytopythium Species Involved in the Establishment and Development of Kiwifruit Vine Decline Syndrome

Abstract: Since 2012, the kiwifruit vine decline syndrome (KVDS) has progressively compromised Italian kiwifruit orchards. Different abiotic and biotic factors have been associated with the establishment and development of KVDS. During monitoring of orchards affected by KVDS in north-western Italy during 2016–2019, 71 Phytopythium spp. were isolated. Based on maximum likelihood concatenated phylogeny on the ITS1-5.8S-ITS2 region of the rDNA, large subunit rDNA, and cytochrome oxidase I, isolates were identified as P. ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…The results are listed in Supplementary Table S4 . Isolates of P. vexans were constantly reisolated from diseased plant roots (sampled from diseased orchards) and identified by using macro- and micromorphological analysis and sequencing, as described in Prencipe et al (2023) . Five representative isolates were deposited in the Turin University Culture Collection (TUCC; Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results are listed in Supplementary Table S4 . Isolates of P. vexans were constantly reisolated from diseased plant roots (sampled from diseased orchards) and identified by using macro- and micromorphological analysis and sequencing, as described in Prencipe et al (2023) . Five representative isolates were deposited in the Turin University Culture Collection (TUCC; Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in Northwestern Italy, which included the orchards considered in this study, revealed a high occurrence of Phytopythium spp. isolated from the root tissues of kiwi plants showing clear symptoms of KVDS ( Prencipe et al, 2023 ). These findings complement the metabarcoding results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations